Modelagem evolucionária da dinâmica industrial (Parte 2): Trajetórias tecnológicas, capacidade de absorç\~ao e aprendizado - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Technological changes are understood as part of a learning process. Even if a share of knowledge is built outside organizations, the adoption and diffusion of new technologies go through the ability of agents to absorb and retain information. Managerial ability to decode external information and increase at the same time productivity is related to how economic agents absorb knowledge. This study aims to continue the literature review that begun in Part 1, which focused on the Schumpeterian competition, technological regimes and diffusion of new knowledge. This article analyzes the main models that address to technological trajectories, absorptive capacity and learning process. After reading both parts (1 and 2), it is clear the importance of these evolutionary concepts for understanding capital accumulation and growth productivity.
Keywords: B52; O3; O33; 330; evolutionary economics; technological change; innovation